Does board independence substitute for external audit quality? Evidence from an exogenous regulatory shock - Pornsit Jiraporn (2019)
© 2017, © The Author(s) 2017. Exploiting the passage of the Sarbanes–Oxley Act (SOX) as an exogenous regulatory shock, we investigate whether board independence substitutes for external audit quality. Based on over 14,000 observations across 18 years, our difference-in-difference estimates show that firms forced to raise board independence are far less likely to employ a Big 4 auditor. In particular, board independence lowers the propensity to use a Big 4 auditor by approximately 38%. Firms with stronger board independence enjoy more effective governance and therefore do not need as much external audit quality as those with less effective governance do. Based on a natural experiment, our empirical strategy is far less vulnerable to endogeneity and is thus considerably more likely to show a causal effect, rather than merely an association.